2009
DOI: 10.1261/rna.1703809
|View full text |Cite
|
Sign up to set email alerts
|

The GW182 protein family in animal cells: New insights into domains required for miRNA-mediated gene silencing

Abstract: GW182 family proteins interact directly with Argonaute proteins and are required for miRNA-mediated gene silencing in animal cells. The domains of the GW182 proteins have recently been studied to determine their role in silencing. These studies revealed that the middle and C-terminal regions function as an autonomous domain with a repressive function that is independent of both the interaction with Argonaute proteins and of P-body localization. Such findings reinforce the idea that GW182 proteins are key compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 45 publications
(182 reference statements)
5
166
0
4
Order By: Relevance
“…GW182 belongs to an evolutionary conserved family with three paralogs in vertebrates including Tnrc6a/GW182, Tnrc6b, and Tnrc6c (6). Results from in vitro studies showed that all three GW182 family members associate with Argonaute family members in the RISC (7)(8)(9)(10) to repress translation or promote mRNA degradation. In addition, knockdown of individual GW182 family members partially impaired miRNA-or siRNA-mediated gene silencing without affecting miRNA biogenesis or stability, indicating redundant roles of GW182 family members in controlling miRNA function (6,11,12).…”
mentioning
confidence: 99%
“…GW182 belongs to an evolutionary conserved family with three paralogs in vertebrates including Tnrc6a/GW182, Tnrc6b, and Tnrc6c (6). Results from in vitro studies showed that all three GW182 family members associate with Argonaute family members in the RISC (7)(8)(9)(10) to repress translation or promote mRNA degradation. In addition, knockdown of individual GW182 family members partially impaired miRNA-or siRNA-mediated gene silencing without affecting miRNA biogenesis or stability, indicating redundant roles of GW182 family members in controlling miRNA function (6,11,12).…”
mentioning
confidence: 99%
“…Finally, there is evidence that in addition to the N-terminal AGO1-binding domain, the middle and C-terminal regions of GW182 (also referred to as bipartite silencing domain) are essential for silencing. 10 Taken together, these results indicate that miRNA-mediated gene silencing is achieved by AGO1 in complex with GW182 independent of its localization to P-bodies. 12 Megha Ghildiyal from Phil Zamore's group (University of Massachusetts, Worcester, MA) presented her recently published findings that in Drosophila melanogaster small RNAs are distributed among Ago1 and Ago2 according to their duplex structure and the identity of their first nucleotide.…”
Section: The Argonaute Worldmentioning
confidence: 74%
“…translational repression and mRNA degradation. 10,11 To further elucidate the role of the GW182-AGO1 interaction in these mechanisms, Elisa Izaurralde (MPI for Developmental Biology, Tübingen, Germany) and her group generated interaction-incapable protein mutants to perform complementation assays. They could show that the N-terminal domain of GW182 which interacts with AGO1 is required for the silencing of miRNA targets.…”
Section: The Argonaute Worldmentioning
confidence: 99%
“…However, knockdown of TNRC6A failed to increase the amount of TRAF3 proteins. In mammals, GW182 protein family has three paralogs named TNRC6A, B, and C. Because they have redundant functions in miRNA pathway, the depletion of TNRC6A alone may not be enough to inhibit the assembly of miRISC and general miRNA pathway (27). To further investigate whether UBR5 regulates TRAF3 through miRNAmediated gene silencing pathway, we generated Firefly luciferase reporter plasmid (Luc-TRAF3 3' UTR) in which a 5' proximal part of 3' untranslated region (3' UTR) of TRAF3 is attached to 3' end of Firefly luciferase gene.…”
Section: Ubr5 Negatively Regulates Traf3-tbk1mentioning
confidence: 99%